Nab-paclitaxel monotherapy as a treatment of patients with metastatic breast cancer in routine clinical practice - Aigner, Julia; Marmé, Frederik; Smetanay, Katharina; Schütz, Florian; Jäger, Dirk; Schneeweiss, Andreas (Anticancer research, 2013)
Aim: To compare treatment results with use of nab-paclitaxel in routine clinical practice with data obtained from clinical trials. Patients and Methods: A retrospective chart review of all 36 patients with metastatic breast cancer treated with nab-paclitaxel was performed. Nab-paclitaxel was given weekly and usually started at 150 mg/m2. Results: Thirteen (36.1%) patients received nab-paclitaxel as first-line, seven (19.4%) as second-line and 16 as third- or further line treatment. Overall, the response rate was 9.7%, disease control rate 64.5%, median progression-free survival 7.5 months and median overall survival 14.2 months. The most frequent non-hematological toxicities of grade 3 or more were fatigue (27.8%), dyspnea, rash and arthalgia (all 5.6%). Six (16.7%) patients developed peripheral neuropathy of grade 2 or more. Incidence of neutropenia grade 3 or more was 41.7% with no case of febrile neutropenia. Conclusion: According to our experience, weekly nab-paclitaxel is effective and tolerable, with results at least comparable to those from the prospective clinical trials.